Comparison of graft and patient outcomes following kidney transplantation in extended hour and conventional haemodialysis patients. Issue 1 (16th December 2018) - See, Emily J; Hawley, Carmel M; Cho, Yeoungjee; Toussaint, Nigel D; Agar, John WM; Pascoe, Elaine M; Lim, Wai H; Francis, Ross S; Collins, Michael G; Johnson, David W
ABSTRACT: Aim: Differences in early graft function between kidney transplant recipients previously managed with either haemodialysis (HD) or peritoneal dialysis are well described. However, only two single‐centre studies have compared graft and patient outcomes between extended hour and conventional HD patients, with conflicting results. Methods: This study compared the outcomes of all extended hour (≥24 h/week) and conventional HD patients transplanted in Australia and New Zealand between 2000 and 2014. The primary outcome was delayed graft function (DGF), defined in an ordinal manner as either a spontaneous fall in serum creatinine of less than 10% within 24 h, or the need for dialysis within 72 h following transplantation. Secondary outcomes included the requirement for dialysis within 72 h post‐transplant, acute rejection, estimated glomerular filtration rate at 12 months, death‐censored graft failure, all‐cause and cardiovascular mortality, and a composite of graft failure and mortality. Results: A total of 4935 HD patients (378 extended hour HD, 4557 conventional HD) received a kidney transplant during the study period. Extended hour HD was associated with an increased likelihood of DGF compared with conventional HD (adjusted proportional odds ratio 1.33; 95% confidence interval 1.06–1.67). There was no significant difference between extended hour and conventional HD in terms of any of the secondary outcomes. Conclusion: Compared to conventional HD, extended hour HD was associated with DGF, although long‐term graft and patient outcomes were not different. Summary at a Glance: In this retrospective study on a large number of patients in the ANZDATA Registry, observation about the graft and patient outcomes following kidney transplantation was compared and reported in extended hour and conventional HD patients. An association of delayed graft function in extended hour haemodialysis patients was noted.